Efforts to Improve Investment Knowledge Through Mentoring for PT. Medikarya Utama Employees - Baity, Namira Nur; Wijaya, Uki Budi; Malik, Muhamad Abdul; Augustin, Lestari; Azizah, Suli Nur; Bastiansyah, Dodi; Suripto, Suripto; Holiawati, Holiawati (Institut Bisnis dan Informatika Kesatuan, 2024)
Investment is a vital step toward achieving long-term financial freedom, particularly for the employees of PT. Medikarya Utama, who encounter modern financial challenges. By investing, employees can grow their assets, safeguard their purchasing power against inflation, and expedite the realization of financial goals, such as retirement savings or funding their children’s education. However, a lack of financial literacy often serves as a barrier to starting the investment process. The Community Service (PKM) program conducted at PT. Medikarya Utama in Cicurug, Sukabumi, aims to enhance investment literacy and raise employee awareness about the significance of effective financial management. Through a combination of lectures, discussions, and counseling sessions, employees gained insights into various investment instruments and learned how to utilize them judiciously. The outcomes of the program showed a marked improvement in participants’ understanding of the importance of investing, with many employees expressing readiness to embark on their investment journeys. This initiative is anticipated to positively impact the financial well-being of employees and contribute to the economic growth of the Sukabumi region.